Diverse human dimensions affect the management of public and animal health impacts of free-roaming dogs in Australia: a One Health solution - Fleming, Peter J. S.; Allen, Benjamin L.; Ballard, Guy; Behrendorff, Linda; Claridge, Andrew W.; Gentle, Matthew N.; Harriott, Lana; Hine, Donald W.; Jenkins, David J.; Kennedy, Brooke P. A.; McLeod, Lynette J.; Meek, Paul D.; et al. (Frontiers in Veterinary Science, 2025)
The socio-ecological roles and status of free-roaming dogs (Canis familiaris) in Australian urban, peri-urban and other environments are complex. We review and synthesise those complexities and identify knowledge deficits and impediments to adoption of best-practice management of free-roaming dogs. Briefly, perceptions of the roles and impacts of free-roaming dogs in Australia are affected by their status as native, introduced and culturally significant animals, the situations in which they occur and the other species, including humans, with which they interact. Their negative, neutral and positive impacts often occur contemporaneously making free-roaming dogs a ‘wicked’ problem. We propose and evaluate a One Health-based solution using an environmental psychology perspective in a strategic adaptive management framework. This includes: a typology of free-roaming dogs that assists in the situational definition of animal and public health and welfare issues; identification of some human dimensions affecting management of free-roaming dogs; identification of discipline specialities that require inclusion in an effective One Health approach; audience segmentation, and; priorities for research and policy development to encourage adoption of best-practice management for each occurrence of free-roaming dog impacts.